Contesting the Exegetical Approaches of Muhammad Abduh and Fazlur Rahman to the Qur’ān - Maghribi, Hamdan; Hidayah , Alfina (Religia: Jurnal Ilmu-Ilmu KeIslaman, 2023)
The exegetical approaches that Muhammad Abduh and Fazlur Rahman used to study the Qur’ān are thisstudy’s main focus of discussion. The research is essential to enrich the literature of contemporary Islamicstudies by contesting the two scholars’ interpretation approaches. This article will answer whether or not thecontextualized interpretation model is still relevant today by comparing and contrasting Abduh andRahman’s respective interpretive approaches and providing examples of the verses mentioned. Hence, thisstudy is a qualitative-library research, whereas data processing relies on content analysis and comparativemethods. Nevertheless, reading Abduh and Rahman’s ideas within contemporary situations is still necessarybecause of its rational-contextual interpretation compatible with modern society and needs. This studysignificantly contributes to contemporary Islamic studies by offering new perspectives on the relevance andapplication of contextualized interpretive models in the modern era.